On the use of haptic tablets for UGV teleoperation in unstructured environments: system design and evaluation - Luz, R.; Corujeira, J.; Grisoni, L.; Giraud, F.; Silva, J. L.; Ventura, R. (IEEE Access, 2019)
Teleoperation of Unmanned Ground Vehicles (UGVs), particularly for inspection of unstructured and unfamiliar environments still raises important challenges from the point of view of the operator interface. One of these challenges is caused by the fact that all information available to the operator is presented to the operator through a computer interface, providing only a partial view of the robot situation. The majority of existing interfaces provide information using visual, and, less frequently, sound channels. The lack of Situation Awareness (SA), caused by this partial view, may lead to an incorrect and inefficient response to the current UGV state, usually confusing and frustrating the human operator. For instance, the UGV may become stuck in debris while the operator struggles to move the robot, not understanding the cause of the UGV lack of motion. We address this problem by studying the use of haptic feedback to improve operator SA. More precisely, improving SA with respect to the traction state of the UGV, using a haptic tablet for both commanding the robot and conveying traction state to the user by haptic feedback. We report (1) a teleoperating interface, integrating a haptic tablet with an existing UGV teleoperation interface, and (2) the experimental results of a user study designed to evaluate the advantage of this interface in the teleoperation of a UGV, in a search and rescue scenario. Statistically significant results were found supporting the hypothesis that using the haptic tablet elicits a reduction in the time that the UGV spends in states without traction.